Parenting the Art of Managing Emotions and Communication with Children to Build a Happy Family - Susan Maulani; Revita Yanuarsari; Ari Abdul Kohar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Emotional management and effective communication between parents and children are key elements in creating a harmonious and happy family. However, many parents still face challenges in understanding and implementing these two aspects optimally. This community service activity aims to improve parents' understanding and skills in managing emotions and building positive communication with children. This program is implemented through a participatory approach that includes educational seminars, group discussions, and interactive simulations. The activities were designed to provide participants with practical insights and encourage direct application in daily life. The results of the activities showed a significant increase in parents' understanding of the importance of emotional management and effective communication, as evidenced by the pre- and post-program evaluations. Parents also reported positive changes in their relationships with their children, such as reduced conflict and increased emotional warmth in the family. In conclusion, the program successfully helped parents understand the importance of parenting as an art and a strategic step toward creating a happier and more supportive family environment. The findings are expected to inspire the development of similar programs in the wider community.